National Language Model of the Society in I. Nechui-Levytskyi's Works (Linguostylistic Studies, 2017)
The article attempts to outline the national language model of the Ukrainian society in the second half of the 19th and the beginning of the 20th centuries on the case study of the   I.Nechuy-Levytsky’s works. It has been revealed that the linguistic image of the European-type of the Ukrainian intellectual determines the basis of this model. The author argues that identified in the I.Nechui-Levytskyi's literary texts words like intellectuals, Europeans, narodovtsi, nationalists, culturalists, including the attributive word-combinations such as intelligent people, an intelligent person expand the imaginary paradigm of the considered linguistic image among the readers. The author draws conclusion that the concept of Ukrainian language, culture and education is also crucial for modeling the national language pattern of the then Ukrainian society.
Keywords: I. Nechui-Levytskyi's works; Ukrainian intellectual prose; national language model; concept; semantic structure of the concept